The complete nucleotide sequence of the chick a-actin gene and its evolutionary relationship to the actin gene family. - Fornwald, J A (1982)
The nucleotide sequence of the chick a-actin gene reveals that the gene is comprised of 7 exons separated by six very short intervening sequences (IVS). The first IVS interrupts the 73 nucleotide 5' untranslated segment between nucleotides 61 and 62. The remaining IVS interrupt the translated region at codons 41/42, 150, 204, 267, and 327/328. The 272 nucleotide 3' untranslated segment is not interrupted by IVS. The amino acid sequence derived from the nucleotide sequence is identical to the published sequence for chick a-actin except for the presence of a met-cys dipeptide at the amino-terminus. The IVS positions in the chick a-actin gene are identical to those of the rat a-actin gene. While there is partial coincidence of the IVS in the a-actin genes with the vertebrate b-actin genes and 2 sea urchin actin genes, there is no coincidence with actin genes from any other source except soybean where one IVS position is shared. This discordance in IVS positions makes the actin gene family unique among the eucaryotic genes analyzed to date.